A Cyclic Pentapeptide Derived from the Second EGF-Like Domain of Factor VII Is an Inhibitor of Tissue Factor Dependent Coagulation and Thrombus Formation - Örning, Lars; Fischer, Peter M.; Hu, Chih-Kao; Agner, Erik; Engebretsen, May; Husbyn, Mette; Petersen, Lizette B.; Ørvim, Una; Llinas, Miguel; Sakariassen, Kjell S. (Thrombosis and Haemostasis, 2002)
We have previously reported the finding of a cyclic dodecapeptide representing loop I of the second EGF-like domain of FVII, which inhibited TF-dependent FX activation (Örning et al. 1997). The biological activity was localized to the tripeptide motif, Glu-Gln-Tyr. We have now synthesized a cyclic analog of this motif, Cys-Glu-Gln-Tyr-Cys (PN7051), evaluated its anticoagulant and antithrombotic properties and performed a detailed structural characterization of the peptide.PN7051 is a dose-dependent inhibitor of TF-dependent FX activation and coagulation of plasma with IC50 values of 10 ± 2 µM and 1.3 ± 0.2 mM, respectively. It shows inhibitory efficacy on acute thrombus formation in an ex vivo model of human thrombosis using native blood. Fibrin deposition, platelet-fibrin adhesion, platelet-thrombus formation, and thrombin-antithrombin complex formation were all inhibited by PN7051 at IC50 values between 0.3 and 0.7 mM. The cyclic peptide is a non-competitive inhibitor of FX activation with no significant activesite effects on FXa or FVIIa, indicating it affects FVII/TF/FX complex formation and function. Studies on the structure activity relationship revealed that Gln3-Tyr4, but not Glu2 were of importance for inhibition. In line with biological results, NMR measurements of PN7051 suggested that the Gln and Tyr residues configure a structural feature that contributes to the anticoagulant activity. Modeling of the Glu99Gln100Tyr101 motif in FVII and comparison with the solution structure of PN7051 suggest that the cyclic pentapeptide exerts its antithrombotic effect by interfering with the docking of Tyr101 into a hydrophobic pocket in the catalytic domain thereby disrupting an essential interaction between the second EGF-like and the catalytic domains of FVII.
Keywords: Factor VII; antithrombotic; ex vivo